A Nonlocal Cauchy Problem for Fractional Integrodifferential Equations - Fang Li; Jin Liang; Tzon-Tzer Lu; Huan Zhu (Journal of Applied Mathematics)
This paper is concerned with a nonlocal Cauchy problem for fractional integrodifferential equations in a separable Banach space X. We establish an existence theorem for mild solutions to the nonlocal Cauchy problem, by virtue of measure of noncompactness and the fixed point theorem for condensing maps. As an application, the existence of the mild solution to a nonlocal Cauchy problem for a concrete integrodifferential equation is obtained.